Answer:
a) The coordinates are (0.431, -2.646) and (3.568,-7.354)
b) The tangent lines are
l₁ = (x-0.431)*2/3 - 2.646
l₂ = (x-3.568)2/3 - 7.354
Step-by-step explanation:
First, lets complete squares, by taking for each cordinate the square of a linear expression
0= x²−4x+y²+10y+13 = (x-2)²+ 4 + (y+5)²-25+13 = (x-2)²+(y+5)² - 8
Hence (x-2)² + (y+5)² = 8
Lets put y in function of x. We should obtain 2 functions f and g that represent the circle.
(y+5)² = 8 - (x-2)² = -x² + 4x + 4
![y = ^+_- \sqrt{-x^2+4x+4} -5](https://tex.z-dn.net/?f=%20y%20%3D%20%5E%2B_-%20%5Csqrt%7B-x%5E2%2B4x%2B4%7D%20-5%20)
Thus
![f(x) = \sqrt{-x^2+4x+4} - 5](https://tex.z-dn.net/?f=%20f%28x%29%20%3D%20%5Csqrt%7B-x%5E2%2B4x%2B4%7D%20-%205%20)
![g(x) = -\sqrt{-x^2+4x+4} - 5](https://tex.z-dn.net/?f=%20g%28x%29%20%3D%20-%5Csqrt%7B-x%5E2%2B4x%2B4%7D%20-%205%20)
Lets find the derivate of each function and the points in which they reach the value 2/3. In those points the tangent line will have a slope of 2/3.
We may just find the values of x which the derivate of f is either 2/3 or -2/3.
![\frac{-x+2}{\sqrt{-x^2+4x+4}} = ^+_-\frac{2}{3} \Leftrightarrow \frac{x^2-4x+4}{-x^2+4x+4} = \frac{4}{9} \Leftrightarrow 9(x^2-4x+4) = 4(-x^2+4x+4) \\\Leftrightarrow 13x^2-52x+20 = 0](https://tex.z-dn.net/?f=%5Cfrac%7B-x%2B2%7D%7B%5Csqrt%7B-x%5E2%2B4x%2B4%7D%7D%20%3D%20%5E%2B_-%5Cfrac%7B2%7D%7B3%7D%20%5CLeftrightarrow%20%5Cfrac%7Bx%5E2-4x%2B4%7D%7B-x%5E2%2B4x%2B4%7D%20%3D%20%5Cfrac%7B4%7D%7B9%7D%20%5CLeftrightarrow%209%28x%5E2-4x%2B4%29%20%3D%204%28-x%5E2%2B4x%2B4%29%20%5C%5C%5CLeftrightarrow%2013x%5E2-52x%2B20%20%3D%200)
The quadratic has roots
![\frac{52 ^+_-\sqrt{1664}}{26}](https://tex.z-dn.net/?f=%20%5Cfrac%7B52%20%5E%2B_-%5Csqrt%7B1664%7D%7D%7B26%7D%20)
one root is 3.568, which corresponds with g, and the other root is 0.431, corresponding to f.
Also g(3.568) = - 7.354 and f(0.431) = -2.646
This means that the coordinates are (0.431 , -2.646), (3.568 , -7.354) and the tangent lines are
l₁ = (x-0.431)*2/3 - 2.646
l₂ = (x-3.568)2/3 - 7.354